Qualidade de vida e depressão em docentes da área da saúde do Campus de São Cristovão da Universidade Federal de Sergipe - Andrade, Viviane Freitas (2016)
The teaching profession is responsible for training professionals from various fields of knowledge; however, exercising the magisterium is an old function and problems generated also have followed it. In this sense, the accumulation and variety of its functions can trigger overload and make them susceptible to work-related stress, identified as a risk factor for depression. In this aspect, the practice of health care teachers are doubly subject to emotional distress situations, since it is generated by the need that the teacher has to be caregiver during the process of teaching and learning. Depression is a syndrome characterized by mood swings that still compromises the quality of life (QoL). The overall objective of the study was to assess the QoL and depression in teaching in the area of Health in the São Cristóvão Campus at UFS. This is a descriptive, cross-sectional study, with a quantitative approach. The convenience sample consisted of 146 teachers. We used three data collection instruments, the Whoqol-Bref, Beck Depression Inventory and a sociodemographic questionnaire prepared by the researchers. The collecting took place from February to November 2015. The data were analyzed descriptively and analytically. The results show that 58.2% of respondents are female, with a mean age of 44.44 years old, 54.8% Caucasian, 63% married, 56.16% doctors, 52.05% full-time commitment, 70.5% dissatisfied with working conditions, 78.8% dissatisfied with pay, 68.5% practice physical activity and 98% practice leisure activities. The results of two general questions of the Whoqol-Bref showed that most of the teachers have positive perception of their QoL (84.9%) and were satisfied with their health (67.8%). The prevalence of teachers with depression was 29.5%. It was concluded that the teachers presented, on a larger scale, satisfaction with their QoL and health. However, the prevalence of depression was high and was associated with QoL, dissatisfaction of working conditions and leisure activities. Therefore, it suggests that depression can have a negative effect on the QoL of individuals, dissatisfaction with working conditions may be associated the development or worsening of disease, in against departure, the results point to a possible protective effect of leisure activities offer mental health.